Easter Eggs & Art: The Robert J. and Yvonne S. Klancko Collection Presented by the Knights of Columbus Museum - Klancko, Robert J.; Klancko, Yvonne S. (Knights of Columbus Museum, 2006)
Keywords: Art collections; Europe, Eastern; Exhibitions; Exhibitions; Christian art and symbolism; Exhibitions; Easter eggs; Exhibitions; Egg decoration; Exhibitions; Folk art; Exhibitions; Klancko, Yvonne S; Klancko, Robert J; dept.art; faculty_collection

Picturing France in the fifteenth century: The map in BNF MS Fr. 4991 - Serchuk, C. (Imago Mundi, 2006)
A map of France is included in a manuscript, dated to around 1460, entitled A tous nobles, which contains a historical account and genealogy of the French kings. The map was produced in the wake of the Hundred Years War, when conflict with the English challenged both French identity and territory. The map, however, smooths over a century of war to reveal a nation both strong and independent. Through the mapmaker's selection of places, and his use of fluvial boundaries to define the area concerned, he has created an image of France shaped by ideology and history that is wholly in keeping with its location in the manuscript, where the renaming of Gaul as France is described. The map reveals the territory of France to be a critical link between the mythical past and the political present. This connection between history and territory, also reiterated in the text itself, is presented in a graphic format that may be related to contemporary practice of using maps along with legal documents in the resolution of territorial disputes. Seen in the light of the king's claim to the lands ruled by his ancestors, the map thus constitutes a rare medieval example of French national identity expressed in relation to French territory. © 2006 Imago Mundi Ltd.
Keywords: A tous nobles; Aquitaine; Bibliothèque nationale de France MS Fr. 4991; Burgundy; Catherine de Medici; Charles IV; Charles VII; Edward III; Eurasia; Europe; France; Genealogy; Hundred Years War; Jean Boutillier; Litigation; Manuscript illumination; Map signs; Map structure; Marcomir; National identity; Nicolas de Nicolay; Philip VI; Propaganda; Western Europe; dept.art; historical cartography; ideology; map; map graphics